Recurrent Glomus Jugulare Tumor Invading the Cerebellum on 68Ga-DOTATATE PET/CT. (8th May 2022) - Balaban Genc, Zeynep Ceren; Filizoglu, Nuh; Ozguven, Salih
Abstract: Glomus tumors are rare, slow-growing extra-adrenal paragangliomas of the head and neck. Treatment and prevention of neurological deficits become more difficult as these tumors aggressively grow in size and infiltrate adjacent anatomical structures. Because glomus tumors are paragangliomas of neuroendocrine origin, 68 Ga-DOTATATE PET/CT can be used as imaging method in the diagnosis and follow-up. In this case, we presented a recurrent glomus jugulare tumor that invaded to the cerebellum on 68 Ga-DOTATATE PET/CT imaging.